Proses Pembuatan Holder A38 Carbon Steel S45C Pada PT. XYZ - Daffa Miftah Khoirudin; Boni Sena; Reza Setiawan; ujibirrahman (Faculty of Engineering, Universitas Serambi Mekkah, 2024)
This research investigates the manufacturing process of the A38 bracket using S45C carbon steel. This bracket is important in construction and heavy equipment applications to maintain equipment reliability and performance. The methods used include cutting, drilling and turning using CNC machines. The research results show that this process requires high precision to ensure the dimensions and quality of the final product. Dimensional and quality checks are carried out regularly to meet strict technical standards. CNC technology has proven effective in increasing production efficiency and consistency.